ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM INVESTOR PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Kristiana, Vera Anis; Sriwidodo, Untung - (Universitas Slamet Riyadi, 2012)
ABSTRACT This research aim to know influence of Return On Investment (ROI), Return On Equity (ROE), Economic Value Added (EVA), Market Value Added (MVA) and of Earnings Per Share (EPS) to Return Share at manufacturing business. To get and collect data use data of publicized financial statement in BEI, and then will be processed with calculation of SPSS. In this research, method analyze data is doubled linear regression. Result of research indicate that variable of MVA hit by heteroscedastisity so that have to be released from research. By partial from fourth of variable that is ROI, ROE, EVA, and EPS give an significant to share return only EVA and other variable do not significant. By simultaneous result of research indicate that fourth of the variable have significant to share return. And most dominant having an effect on variable is EVA. Keywords: Return On Investment, Return On Equity, Economic Value Added, Market Value Added, Earnings Per Share